1993
DOI: 10.1161/01.cir.87.3.931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective angiotensin II receptor antagonism and angiotensin converting enzyme inhibition on the coronary vasculature in vivo. Intravascular two-dimensional and Doppler ultrasound studies.

Abstract: Thus, these acute studies in anesthetized dogs suggest that inhibition of AT1-receptors in the coronary circulation results in vasodilator responses greater in magnitude than ACE inhibition and partly endothelium dependent. The exact role for AT1-receptors in human coronary physiology and pathology remains to be defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 34 publications
2
28
1
2
Order By: Relevance
“…Cachofeiro et al (1992) have shown in the SHR that the acute reduction in blood pressure induced by the drug is reduced by approximately 60% when the animals are pretreated with L-NMMA. Similar findings have been reported by others (Kumagai et al, 1993;Pollock et al, 1993;Sudhir et al, 1993) and in our study, L-NAME raised blood pressure and vascular resistances in losartan-treated animals. The origin of losartan-mobilized NO is still debated.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Cachofeiro et al (1992) have shown in the SHR that the acute reduction in blood pressure induced by the drug is reduced by approximately 60% when the animals are pretreated with L-NMMA. Similar findings have been reported by others (Kumagai et al, 1993;Pollock et al, 1993;Sudhir et al, 1993) and in our study, L-NAME raised blood pressure and vascular resistances in losartan-treated animals. The origin of losartan-mobilized NO is still debated.…”
Section: Discussionsupporting
confidence: 93%
“…It appears from our study that losartan decreases blood pressure and regional vascular resistances in the pithed SHR which indicates either that AII contributes to the vascular tone in this preparation, or that losartan administration results in the release of vasodilator agents, among which NO (Cachofeiro et al, 1992; Kumagai et al, 1993;Sudhir et al, 1993) and PGs (Jaiswal et al, 1991;Catalioto et al, 1994) have previously been proposed as candidates. Our results also show that losartan significantly reduces or even abolishes the systemic pressor and renal and muscular vasoconstrictor responses elicited by electrical stimulation of the spinal cord but does not affect the simultaneously induced tachycardia, thus confirming the vascular selective sympathoinhibitory effects of the drug (Moreau et al, 1993).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Accumulating bradykinin may lead to increased NO synthesis and activity. 24 Another potential mechanism involves the inhibition of the production of angiotensin II and as a consequence decrease formation of superoxide anion (O − 2 ). It is well known that angiotensin II stimulates the NADH/NAD(P)H oxidase of endothelial and smooth muscle cells.…”
Section: Angiotensin-converting Enzyme (Ace) Inhibitors and Calcium Amentioning
confidence: 99%